Application of sulfur SAD to small crystals with a large asymmetric unit and anomalous substructure. Issue 8 (15th July 2022) - Mou, Tung-Chung; Zeng, Baisen; Doukov, Tzanko I.; Sprang, Stephen R.
Abstract : Multiple approaches to data merging and scaling and anomalous substructure determination were used to solve the structure of a large asymmetric unit from weakly diffracting crystals by sulfur SAD. Abstract : The application of sulfur single‐wavelength anomalous dispersion (S‐SAD) to determine the crystal structures of macromolecules can be challenging if the asymmetric unit is large, the crystals are small, the size of the anomalously scattering sulfur structure is large and the resolution at which the anomalous signals can be accurately measured is modest. Here, as a study of such a case, approaches to the SAD phasing of orthorhombic Ric‐8A crystals are described. The structure of Ric‐8A was published with only a brief description of the phasing process [Zeng et al. (2019), Structure, 27, 1137–1141]. Here, alternative approaches to determining the 40‐atom sulfur substructure of the 103 kDa Ric‐8A dimer that composes the asymmetric unit are explored. At the data‐collection wavelength of 1.77 Å measured at the Frontier micro‐focusing Macromolecular Crystallography (FMX) beamline at National Synchrotron Light Source II, the sulfur anomalous signal strength, |Δano |/σΔano ( d ′′/sig), approaches 1.4 at 3.4 Å resolution. The highly redundant, 11 000 000‐reflection data set measured from 18 crystals was segmented into isomorphous clusters using BLEND in the CCP 4 program suite. Data sets within clusters or sets of clusters were scaled and merged using AIMLESS from CCP 4 or, alternatively, the phenix.scale_and_merge tool from the Phenix suite. The latter proved to be the more effective in extracting anomalous signals. The HySS tool in Phenix, SHELXC / D and PRASA as implemented in the CRANK 2 program suite were each employed to determine the sulfur substructure. All of these approaches were effective, although HySS, as a component of the phenix.autosol tool, required data from all crystals to find the positions of the sulfur atoms. Critical contributors in this case study to successful phase determination by SAD included (i) the high‐flux FMX beamline, featuring helical‐mode data collection and a helium‐filled beam path, (ii) as recognized by many authors, a very highly redundant, multiple‐crystal data set and (iii) the inclusion within that data set of data from crystals that were scanned over large ω ranges, yielding highly isomorphous and highly redundant intensity measurements.